SECONDARY SCHOOL TEACHERS’ PERSPECTIVES ON APPLYING ONLINE TEACHING STRATEGIES DURING COVID-19 PANDEMIC - Khalidyan Nugrahadi Putra; Fatimah Mulya Sari (Proceedings of the International Conference on Literacy and Education, 2022)
The shifting of the teaching-learning process into online learning encourages most English teachers to adapt and employ the proper teaching strategies to achieve the learning goals. This present study aims to investigate the teachers’ perspectives on applying online teaching strategies during the online learning process. A case study was applied in this study and the data were obtained from an observation and a questionnaire that contains two sections including teachers’ teaching strategies in delivering material and providing assignments or projects during the online learning process. The findings show that teachers gave positive responses toward the use of their teaching strategies. In delivering the materials, they applied pre- teaching strategy by mentioning and explaining the topic of their learning material briefly, while-teaching strategies by providing supporting learning media and using interactive teaching strategies, and post-teaching strategies by giving feedback and review of learning materials. On the other hand, they used several strategies when giving assignments and projects to their students by providing individual group works, peer works, and group works. Thus, this study may provide valuable insight for teachers to maintain the efficiency of online learning.